Zmienność genu hormonu wzrostu i jego związek z cechami budowy ciała i użytkowości mięsnej = Variability of growth hormone gene and its association with growth of body and meat production - Habel, Angelika; Górecka, Milena; Duszyńska-Stolarska, Oliwia; Mroczkowski, Sławomir (Journal of Education, Health and Sport, 2015)
Habel Angelika, Górecka Milena, Duszyńska-Stolarska Oliwia, Mroczkowski Sławomir. Zmienność genu hormonu wzrostu i jego związek z cechami budowy ciała i użytkowości mięsnej = Variability of growth hormone gene and its association with growth of body and meat production. Journal of Education, Health and Sport. 2015;5(6):313-320. ISSN 2391-8306. DOI 10.5281/zenodo.18625 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A313-320 https://pbn.nauka.gov.pl/works/566879 http://dx.doi.org/10.5281/zenodo.18625 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 16.06.2015. Zmienność genu hormonu wzrostu i jego związek z cechami budowy ciała i użytkowości mięsnej Variability of growth hormone gene and its association with growth of body and meat production Angelika Habel, Milena Górecka, Oliwia Duszyńska-Stolarska, Sławomir Mroczkowski1 Zakład Genetyki i Podstaw Hodowli Zwierząt, Uniwersytet Technologiczno-Przyrodniczy im. Jana i Jędrzeja Śniadeckich w Bydgoszczy1 Streszczenie: Rozwój genetyki molekularnej umożliwił wytypowanie genów odpowiedzialnych za regulacje wzrostu i rozwoju organizmu. Genem kandydującym, którego produkt białkowy uczestniczy w licznych procesach zachodzących w komórkach ciała, oddziałując na wzrost i metabolizm mięśni szkieletowych, kości, chrząstek i tkanki tłuszczowej jest gen hormonu wzrostu (GH). Wielu badaczy podejmowało i nadal podejmuje trud ustalenia jego wpływu na cechy budowy ciała i użytkowości mięsnej. Liczne badania wskazują na istnienie zależności między polimorfizmem genu GH a produkcją mięsa oraz budową ciała m. in. u świń, bydła, owiec i kóz. Słowa kluczowe: gen hormonu wzrostu, somatotropina, polimorfizm GH. Summary: The development of molecular genetics has allowed predicting genes responsible for regulating growth and development. Candidate gene whose protein product is involved in many processes occurring in the cells of the body, affecting on the growth and metabolism of the skeletal muscle, bone, cartilage and fat cells is a gene of growth hormone (GH). Many researchers undertook and continue to take the trouble to determine its impact on the features of body growth and meat production. Many study suggest a relationship between GH gene polymorphism and the features of meat production and growth traits in pigs, cattle, sheep and goats. Key words: growth hormone gene, somatotropin, GH polymorphism.